Giving Voice to Child Victims: Victim Impact Statements as a Path toward Victim-Centered Justice - Anang Riyan Ramadianto; Suhadi; Indah Sri Utari; Eva Syahidah (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2026)
Sexual violence against children constitutes a grave violation of human dignity and causes long-term psychological and developmental harm. Although Indonesia’s Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) reflects a victim-oriented substantive framework, criminal procedure law remains largely offender-centered. Neither the current nor the newly enacted Criminal Procedure Code recognizes the Victim Impact Statement (VIS) as a formal mechanism for conveying victims’ experiences during criminal proceedings. This study examines the urgency of VIS in realizing victim-centered justice and formulates a regulatory model for its integration into UU TPKS. Using normative juridical research with statutory, conceptual, and comparative approaches, the study analyzes relevant legislation, judicial regulations, and scholarly literature. The findings reveal a regulatory gap between substantive victim protection and procedural mechanisms. This article proposes standardized VIS provisions to strengthen restorative justice and ensure judicial decisions reflect the recovery and dignity of child victims.